The tectonic evolution of a critical segment of the Dinarides‐Alps connection: Kinematic and geochronological inferences from the Medvednica Mountains, NE Croatia. Issue 9 (28th September 2015) - van Gelder, I. E.; Matenco, L.; Willingshofer, E.; Tomljenović, B.; Andriessen, P. A. M.; Ducea, M. N.; Beniest, A.; Gruić, A.
Abstract The transition zone between the Alps and Dinarides is a key area to investigate kinematic interactions of neighboring orogens with different subduction polarities. A study combining field kinematic and sedimentary data, microstructural observations, thermochronological data (Rb‐Sr and fission track), and regional structures in the area of Medvednica Mountains has revealed a complex polyphase tectonic evolution. We document two novel stages of extensional exhumation. The first stage of extension took place along a Late Cretaceous detachment following the late Early Cretaceous nappe stacking, burial, and greenschist facies metamorphism. Two other shortening events that occurred during the latest Cretaceous‐Oligocene were followed by a second event of extensional exhumation, characterized by asymmetric top‐NE extension during the Miocene. Top‐NW thrusting took place subsequently during the Pliocene inversion of the Pannonian Basin. The Cretaceous nappe burial, Late Cretaceous extension, and the Oligocene(‐Earliest Miocene) contraction are events driven by the Alps evolution. In contrast, the latest Cretaceous‐Eocene deformation reflects phases of Dinaridic contraction. Furthermore, the Miocene extension and subsequent inversion display kinematics similar with observations elsewhere in the Dinarides and Eastern Alps. All these processes demonstrate that the Medvednica Mountains were affected by Alpine phases of deformations to a much higher degree than previously thought. Similarly with what has been observed in other areas of contractional polarity changes, such as the Mediterranean, Black Sea, or New Guinea systems, the respective tectonic events are triggered by rheological weak zones which are critical for localizing the deformation created by both orogens.